Femtosecond Laser Versus Mechanical Microkeratome in Thin-Flap Laser in Situ Keratomileusis (Lasik) for Correction of Refractive Errors an Evidence-Based Effectiveness and Cost Analysis - Mostafaie, Ali; Mahboub Ahari, Alireza; Sadeghi Ghyassi, Fatemeh; Hajebrahimi, Sakineh; Yousefi, Mahmoud (Journal of Lasers in Medical Sciences, 2011)
INTRODUCTION: To compare the efficacy and cost-effectiveness of Femtosecond laser versus mechanical Microkeratome corneal flap creation in correction of refractive errors. METHODS: I this review, a comprehensive search of Medline, SCOPUS, Cochrane, TRIP database, supplemented by HTA and economic databases was performed. We searched for randomized controlled trials (RCTs) of Femtosecond laser which included mechanical Microkeratome in other arm. The quality of the retrieved studies was appraised by two independent reviewers and appropriate articles were finalized. RESULTS: A total of 1142 articles were identified, of which, 1059 were excluded after review of the titles and abstracts and 83 articles remained. Systematic reviews and RCTs were evaluated through CASP international worksheet. Eventually, 61 titles were excluded, leaving 22 articles to be reviewed. Safety: There was no individual evidence to cover all safety components about Femtosecond laser, but in summary, this modality seems a safe method for corneal flap creation. Effectiveness: No statistically significant difference was shown in visual acuity and refractive errors. The important secondary end point of this review was diffuse Lamellar keratitis in 17% of the femtosecond group versus 5% in mechanical Microkeratome. Inflammation was low-grade and improved during the first 3 months of follow-up period with a low dose medication without corneal scarring. The two groups was comparable in all clinical outcomes including Unorrected Visual Acuity (UCVA), Best Special Corrected Visual Acuity (BSCVA), manifest refraction, wave front aberrometry, Schirmer test, and Tear Break up time (TBUT). Cost Analysis: Results showed that marginal cost incurred due to Femtosecond technology adoption may vary from 27 to 117 € (resulted from sensitivity analysis). It is clear that additional cost may be a small proportion of LASIK procedure total cost. CONCLUSION: Although Femtosecond flap creation is a modern method with a good quality of corneal flap, but, there is no high-quality evidence to show superiority of Femtosecond laser in clinical outcomes. Although the efficacy and cost of the systems is almost equal, traditional method still remains as the standard approach.